İnönü Üniversitesi Tıp Fakültesi 1. ve 6. Sınıf Öğrencilerinin Gözünden Hekime Şiddet Nedenleri - Tetik, Burcu Kayhan; Bağ, Harika Gözükara; Paksoy, Nur; Tural, Cansu; Gedik, Işılay; Sertkaya, Serap (Acıbadem Mehmet Ali Aydınlar Üniversitesi, 2018)
Amaç: Bu çalışmanın amacı 1. ve 6. Sınıf tıp fakültesi öğrencilerinin gözünden hekime şiddet nedenlerini araştırmak, bu konudaki bilgi düzeylerini belirleyebilmek ve sağlıkta şiddet ile ilgili farkındalıklarını artırabilmektir.Gereç - Yöntem: İnönü Üniversitesi Tıp Fakültesi 1. ve 6. Sınıf öğrencilerinden çalışmaya katılmayı kabul eden 246 öğrenci alınmıştır. Hekime neden şiddet uygulanabileceği ile ilgili hazırlanan sorulardan oluşan anket uygulanmıştır. Veriler SPSS 22 prog ile değerlendirilmiştir.Bulgular: Çalışmaya toplam 246 öğrenci katılmıştır. Öğrencilere en yaygın şiddet sebeplerinin ne olduğu sorulduğunda, dönem 1 öğrencilerinin %26.8’i, dönem 6 öğrencilerinin %61.3’ü “Muayene olmak için hastanın çok bekletilmesi” cevabını vermiş ve bu fark istatistiksel olarak anlamlı kabul edilmiştir p

Objectives: This study is aimed to investigate the considerations of the 1st-year and the 6th-year medical students at Inonu University on the causes of violence against doctors and medical staff , to determine their knowledge level of this issue and to raise their awareness with regards to violence within the health sector.Material-Method: A total of 246 1st-year and 6th-year medical students from Inonu University Medicine Faculty who agreed to participate this research were included into the study. A survey related to why the doctors were likely to get exposed to violence was conducted. The data analysis was performed with SPSS 22 software. Results: 246 medical students participated in the study. When the students were asked about the most common violence causes, 26.8% of the 1st-year and 61.3% of the 6th-year students responded “the patients’ being kept waiting for the medical examination”, and 28.8% of the 1st-year and 8.6% of the 6th-year students replied as “doctors’prescribing medications without examining the patients”, which were regarded statistically significant p
The Considerations of The 1St-Year and The 6Th-Year Medical Students At Inonu University On The Causes of Violence Against Medical Staff